BINGKAI SUMATERA BROADCAST ON DAAI TV MEDAN AS A MEDIUM FOR SOCIAL AND HUMANITARIAN EDUCATION FOR THE COMMUNITY OF MEDAN CITY - Hotmayjar Ardila Dalimunthe; Abdul Rasyid (Journal Analytica Islamica, 2026)
This study examines how Bingkai Sumatera on DAAI TV Medan functions as a medium of social and humanitarian education in Medan City. Previous studies on television journalism have largely focused on commercial logic, sensationalism, or information delivery, while limited attention has been given to how local television constructs humanitarian narratives and diffuses social values to urban audiences. Using a descriptive qualitative approach, this study applies Robert Entman’s framing theory and Everett Rogers’ diffusion of innovations theory. Data were obtained through interviews with the editorial team, audience responses, and documentation of selected broadcasts. The findings show that Bingkai Sumatera frames social issues by emphasizing resilience, dignity, and empowerment rather than victimization. This framing strategy positions marginalized subjects as active social actors and encourages audiences to develop more empathetic and inclusive interpretations. The study also finds that the program works not only as a source of information but also as a channel for diffusing humanitarian values in everyday media consumption. Academically, this research contributes to communication studies by demonstrating how local television can operate as a site of humanistic journalism and social education beyond commercial media logic.